Tipping the MYC–MIZ1 balance: targeting the HUWE1 ubiquitin ligase selectively blocks MYC‐activated genes - Franz X Schaub; John L Cleveland (EMBO Molecular Medicine)
Abstract MYC family oncoproteins (MYC, N‐MYC and L‐MYC) function as basic helix‐loop‐helix‐leucine zipper (bHLH‐Zip) transcription factors that are activated (i.e., overexpressed) in well over half of all human malignancies (Boxer & Dang, 2001; Beroukhim et al, 2010). In this issue of EMBO Molecular Medicine, Eilers and colleagues (Peter et al, 2014) describe a novel approach to disable MYC, whereby inhibition of the ubiquitin ligase HUWE1 stabilizes MIZ1 and leads to the selective repression of MYC‐activated target genes.